Troponin dan Manajemen Iskemia Miokardium Perioperatif - Leksana, Ery; Purnomo, Ika Cahyo (Majalah Anestesia dan Critical Care, 2014)
Penyakit jantung iskemik sering memberikan gambaran dan perkembangan yang membahayakan. Kejadian dari tahun ke tahun terus meningkat dan menyumbang angka mortalitas yang tinggi. Angina pectoris, gambaran iskemia pada EKG, dan peningkatan petanda jantung menunjukkan terjadinya infark miokard akut. Pasien dalam kondisi demikian sangat berisiko untuk menjalani proses pembiusan. Pemeriksaan troponin bersenstivitas tinggi telah diperkenalkan, namun hal ini memberikan tantangan yang baru dalam hal sensitivitas vs spesivisitas. Berbagai panduan telah diterbitkan untuk memandu dokter ahli anestesi melewati rintangan risiko pada penderita dengan iskemia miokard. Kata kunci: Anestesi, iskemia miokardium, troponin Troponin and Perioperative Management in Iskemia Myokard Troponin Ischemic heart disease often develop harmful conditions. Incidence from year to year continues to increase and accounted for high mortality rate. Angina pectoris, marked ECG changes and elevation of cardiac markers, especially troponins indicate the presence of acute myocardial infarct. Patients in this condition is very risky to undergo anesthesia process. High sensitivity troponin test were introduced, but it gave new challenge of sensitivity vs specificity. Guidelines have been published to guide the anesthesiologist through the obstacles of risks in patients with myocardial ischemia. Key words: Anesthesia, myocardial ischemia, troponin Reference Wu AH, Apple FS, Gibler WB, Jesse RL, Warshaw MM, Valdes R Jr. National Academy of Clinical Biochemistry Standards of laboratory practice: recommendations for the use of cardiac markers in coronary artery diseases. Clin Chem. Jul 1999;45(7):1104–21. Alpert JS, Thygesen K, Antman E, Bassand JP. Myocardial infarction redefined--a consensus document of The Joint European Society of Cardiology/American College of Cardiology Committee for the redefinition of myocardial infarction. J Am Coll Cardiol. Sep 2000;36(3):959–69. Antman EM. Decision making with cardiac troponin tests. N Engl J Med. Jun 27 2002;346(26):2079–82. Morrow DA, Cannon CP, Jesse RL, Newby LK, Ravkilde J, Storrow AB, dkk. National academy of clinical biochemistry laboratory medicine practice guidelines: clinical characteristics and utilization of biochemical markers in acute coronary syndromes. Clin Chem. Apr 2007;53(4):552–74. Hamm CW, Giannitsis E, Katus HA. Cardiac troponin elevations in patients without acute coronary syndrome. Circulation. Dec 3 2002;106(23):2871–2. Ammann P, Fehr T, Minder EI, Günter C, Bertel O. Elevation of troponin I in sepsis and septic shock.Intensive Care Med. Jun 2001;27(6):965–9. Bakshi TK, Choo MK, Edwards CC, Scott AG, Hart HH, Armstrong GP. Causes of elevated troponin I with a normal coronary angiogram. Intern Med J. Nov 2002;32(11):520–5. Nunes JP, Mota Garcia JM, Farinha RM, dkkl. Cardiac troponin I in aortic valve disease. Int J Cardiol. Jun 2003;89(2–3):281–5. Hamwi SM, Sharma AK, Weissman NJ, Goldstein SA, Apple S, Caños DA. Troponin-I elevation in patients with increased left ventricular mass. Am J Cardiol. Jul 1 2003;92(1):88–90. Velmahos GC, Karaiskakis M, Salim A, Toutouzas KG, Murray J, Asensio J. Normal electrocardiography and serum troponin I levels preclude the presence of clinically significant blunt cardiac injury. J Trauma. Jan 2003;54(1):45–50; discussion 50–1. Smith SC, Ladenson JH, Mason JW, Jaffe AS. Elevations of cardiac troponin I associated with myocarditis. Experimental and clinical correlates. Circulation. Jan 7 1997;95(1):163–8. Brandt RR, Filzmaier K, Hanrath P. Circulating cardiac troponin I in acute pericarditis. Am J Cardiol. Jun 1 2001;87(11):1326–8.